Isolation of Elusive Phosphinidene‐Chlorotetrylenes: The Heavier Cyanogen Chloride Analogues. Issue 54 (10th August 2022) - Nag, Ekta; Francis, Maria; Battuluri, Sridhar; Sinu, Bhavya Bini; Roy, Sudipta
Abstract: The elusive phosphinidene‐chlorotetrylenes, [PGeCl] and [PSiCl] have been stabilized by the hetero‐bileptic cyclic alkyl(amino) carbene (cAAC), N‐heterocyclic carbene (NHC) ligands, and isolated in the solid state at room temperature as the first neutral monomeric species of this class with the general formulae (L)P‐ECl(L′) (E=Ge, 3 a –3 c ; E=Si, 6 ; L=cAAC; L′=NHC). Compounds 3 a –3 c have been synthesized by the reaction of cAAC‐supported potassium phosphinidenides [cAAC=PK(THF) x ] n (1 a –1 c ) with the adduct NHC:→GeCl2 (2 ). Similarly, compound 6 has been synthesized via reaction of 1 a with NHC:→SiCl2 adduct (4 ). Compounds 3 a –3 c, and 6 have been structurally characterized by single‐crystal X‐ray diffraction, NMR spectroscopy and mass spectrometric analysis. DFT calculations revealed that the heteroatom P in 3 bears two lone pairs; the non‐bonding pair with 67.8 % of s‐ and 32 % of p character, whereas the other lone pair is involved in π backdonation to the CcAAC ‐N π* of cAAC. The Ge atom in 3 contains a lone pair with 80 % of s character, and slightly involved in the π backdonation to CNHC . EDA‐NOCV analyses showed that two charged doublet fragments {(cAAC)(NHC)} +, and PGeCl − prefer to form one covalent electron‐sharing σ bond, one dative σ bond, one dative π bond, and a charge polarized weak π bond. The covalent electron‐sharing σ bond contributes to the major stabilization energy to the total orbital interaction energy of 3, enabling the first successful isolations of this class of compounds (3, 6 ) in the laboratory. Abstract : Elusive hetero‐bileptic carbenes‐stabilized singlet phosphinidiene‐chlorosilylene, and chlorogermylenes with majorly contributing covalent electron‐sharing σ bonds are isolated and structurally characterized in the solid state.